Approaches to implementing solid waste recycling facilities - Rogoff, Marc Jay (Noyes Publications, 1994)
This book illustrates practical approaches to recycling solutions, and will provide needed guidance to public officials and other interested parties. This book addresses both art and science aspects of recycling. Many communities are faced with difficult choices when it comes to expanding or maintaining current recycling efforts.
Keywords: Recycling (Waste, etc.); elektronické knihy; electronic books